Maternal mortality at Gulbarga district hospital, a tertiary care centre - Biradar, Sudha V.; Kerure, Rajshekhar D.; Biradar, Amaresh V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy, although being considered a normal physiological state, carries serious risk of morbidity and at times maternal death. Maternal mortality ratio (MMR) is a very sensitive index that reflects the quality of health care provided by the country to the women population. It also reflects the educational and socioeconomic state of a country as well as public health consciousness. This study was carried out to determine the causes of maternal deaths at Gulbarga district hospital, a tertiary care hospital. Methods: This is a cohert of prospective and retrospective hospital based study of 2 years. IPD case records of maternal deaths were studied. A total of 25 maternal deaths were analyzed using percentage. Results: In the maternal deaths studied, the leading direct causes of death were haemorrhage (32%), followed by eclampsia (15%). Anaemia (8%) and cerebrovascular accidents (9%) were the common indirect causes of maternal death in our study. Most women (72%) died within 12 hours of admission suggesting majority patients reach the tertiary care hospital late. Conclusions: Most of the maternal deaths were preventable by optimal antenatal, intranatal and perinatal care. Most effective intervention to reduce pregnancy related mortality is education of family planning methods and safe abortion methods, increasing the number of skilled birth attendants, reducing home births and improving emergency obstetric care (EOC).